CURCUMIN AMENDS OXIDATIVE STRESS AND ANTIOXIDANTS STATUS IN OLFACTORY LOBES, CEREBRUM, HYPOTHALAMUS-HIPPOCAMPUS, CEREBELLUM AND PONS-MEDULLA OF MICE ACUTELY INTOXICATED WITH LINDANE - Chaudhary, Bharti; Agarwal, Sonam; Bist, Renu (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Present study ascertains the neuroprotective potential of curcumin in olfactory lobes, cerebrum, hypothalamus-hippocampus, cerebellum and pons-medulla of mice, intoxicated with lindane. Methods: For the study, mice were divided into four groups. Olive oil was given as a vehicle to the mice of group I. Mice belonging to groups II and III was administered with lindane and curcumin respectively, for 12 h exposure by intraperitoneal injection. In group IV, curcumin was administered 10-15 min prior to exposure of lindane. Results: Lindane exposure significantly increased the activities of thiobarbituric acid reactive substance (TBARS) (p<0.05) and protein carbonyl content (PCC) (p<0.05) whereas decreased the activity of reduced glutathione (GSH) (p<0.05) and superoxide dismutase (SOD) (p<0.05). Treatment of curcumin alone as well as in combination with lindane significantly declined the level of TBARS and PCC (p<0.05) and increased the activity of GSH and SOD (p<0.05). Conclusion: Curcumin has neuroprotective potential. It can be used as a therapeutic agent against lindane induced toxicity. Keywords: Lindane, Curcumin, Oxidative stress, Endogenous antioxidant